Rising possessors in Spanish - Fábregas, Antonio (IBERIA: An International Journal of Theoretical Linguistics, 2011)
In this paper we propose that some nominal structures involve rising of a possessive pronoun from a lower, defective nominal domain to a structure headed by a noun with which they do not hold any direct semantic relation. The conditions under which this operation can take place are explored: it can only happen when the lower domain is severly impoverished, it is introduced by a weak preposition that does not define a phase and when the PP is selected by the head noun as its complement.